Body talk in the digital age: A controlled evaluation of a classroom-based intervention to reduce appearance commentary and improve body image. Issue 1 (May 2021) - Bell, Beth T; Taylor, Caitlin; Paddock, Danielle L.; Bates, Adam; Orange, Samuel T
This research evaluates the efficacy of a classroom-based intervention – Body Talk in the Digital Age (BTIDA) – in reducing adolescents' appearance commentary and improving body image. British adolescents ( N = 314; Age Range = 12–14) were cluster randomised to intervention or waiting-list control groups. Measures of appearance commentary, appearance ideal internalisation, self-objectification and body satisfaction were completed at baseline (T1), then one-week (T2) and eight-week (T3) post-intervention. Multi-level modelling showed girls who received BTIDA reported less appearance commentary engagement and thin ideal internalisation at T2 and T3, than the control, supporting the partial efficacy of BTIDA for girls. No intervention effects were found among boys.